Early sport specialization and subjective hip and groin dysfunction in collegiate ice hockey athletes - Sheppard, M.; Nicknair, J.; Goetschius, J. (Journal of Athletic Training, 2020)
Context: Sport specialization is a popular trend among youth athletes that has been associated with an increased risk for developing lower extremity overuse injuries. Early ice hockey specialization may contribute to the high rates of noncontact and overuse hip and groin injuries in collegiate ice hockey athletes. Objective: To examine the effects of high, moderate, and low levels of sport specialization on subjective hip and groin dysfunction in collegiate ice hockey athletes. Design: Retrospective cohort study. Setting Data were collected during the midseason of the 2018-2019 hockey season at a local ice hockey arena. Patients or Other Participants: National Collegiate Athletic Association Division III and club ice hockey players from Midwestern college programs (n = 187; 81 women, 106 men). Main Outcome Measure(s): Participants were stratified into high-, moderate-, and low-specialization groups based on ice hockey participation before grade 9 of high school. The 6 subscales of the Hip and Groin Outcome Score questionnaire were used to assess current subjective hip and groin dysfunction. Results: The high-specialization group had lower scores than the low-specialization group on the Symptoms (P = .001), Pain (P = .003), Activities of Daily Living (P = .001), Sport and Recreation (P = .014), and Quality of Life (P = .002) subscales. The moderate-specialization group had lower scores than the low-specialization group on the Symptoms (P = .015) and Activities of Daily Living (P = .006) subscales. Conclusions: Collegiate ice hockey athletes who were highly specialized before high school reported greater current hip and groin pain, symptoms, and dysfunction during activities of daily living and sport and recreation and lower current hip- and groin-related quality of life compared with low-specialization ice hockey athletes. Early ice hockey specialization may be detrimental to hip and groin function in collegiate ice hockey athletes.